1998
DOI: 10.1021/jp972565w
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Orbital Calculations of the Potential Energy Surfaces for the N(2D) + CH4 Reaction

Abstract: Ab initio molecular orbital calculations have been carried out on the N( 2 D) + CH 4 reaction in order to obtain information on possible reaction products. Stationary points associated with the product channels and their harmonic vibrational frequencies have been calculated at the MP2(full)/cc-pVTZ level of theory. Barrier heights and heats of reaction have been estimated at the projected MP4(full,SDTQ)/cc-pVTZ level of theory. Among the possible processes considered, the reaction pathways to produce CH 2 NH +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 21 publications
9
65
3
Order By: Relevance
“…As far as reaction (10) is concerned, however, the results of recent reaction dynamics studies do not confirm the assumptions of Yung about the reaction mechanism and the nature of the products. According to the ab initio calculations of the NCH 4 PES [178], the possible products are (10a) CH 3 N + H, (10b) NH + CH 3 , (10c) CHNH 2 + H, and (10d) CH 2 NH + H. A recent spectroscopic study under collision-free conditions [179] derived an absolute yield of 0.3 ± 0.1 for NH (from channel 10b) and 0.8±0.2 for H (from channels 10a, 10c, 10d) production. The nature of the CH 3 N isomer(s) produced in conjunction with H has been established in a CMB-MS study of the N( 2 D) + CH 4 reaction as a function of collision energy (from ~ 20 kJ mol −1 to ~ 60 kJ mol −1 ) [117119,180].…”
Section: Key Results On the Reactions Of Atomic Nitrogen N(2d)mentioning
confidence: 99%
“…As far as reaction (10) is concerned, however, the results of recent reaction dynamics studies do not confirm the assumptions of Yung about the reaction mechanism and the nature of the products. According to the ab initio calculations of the NCH 4 PES [178], the possible products are (10a) CH 3 N + H, (10b) NH + CH 3 , (10c) CHNH 2 + H, and (10d) CH 2 NH + H. A recent spectroscopic study under collision-free conditions [179] derived an absolute yield of 0.3 ± 0.1 for NH (from channel 10b) and 0.8±0.2 for H (from channels 10a, 10c, 10d) production. The nature of the CH 3 N isomer(s) produced in conjunction with H has been established in a CMB-MS study of the N( 2 D) + CH 4 reaction as a function of collision energy (from ~ 20 kJ mol −1 to ~ 60 kJ mol −1 ) [117119,180].…”
Section: Key Results On the Reactions Of Atomic Nitrogen N(2d)mentioning
confidence: 99%
“…Takayanagi et al (1999) In addition to kinetic data, much work has been done on this system at the level of reaction dynamics experiments and theoretical calculations in recent years. The first hint of the reaction mechanism and primary products came from the ab initio calculations by Kurosaki et al (1998) of the relevant potential energy surface. According to those calculations, the exothermic channels are:…”
Section: Reaction N ( 2 D) + Chmentioning
confidence: 99%
“…This is only possible within an intermediate complex, such as the CH 3 NH radical. In fact, somewhat indirect experimental evidence (the analogy with O( 1 D), [7]) as well as theory [11][12][13][14] have shown that such a complex is formed by N( 2 D) insertion into the C-H bond. N( 4 S) and N þ ( 3 P) are not expected to insert in this way, and consequently the CH fragment yield at low energies is small with these two reactants.…”
Section: Resultsmentioning
confidence: 99%
“…There are also many measurements of overall N( 2 D) reaction rate constants in the literature (see [10] and references therein). On the part of theory, potential energy surfaces [11][12][13] plus trajectory studies [14] have shown that N( 2 D) inserts into the C-H bond to form the CH 3 NH intermediate radical, which then fragments into CH 3 N + H or CH 3 + NH. CH 2 NH 2 formation would be energetically slightly favoured over CH 3 NH, but this radical is dynamically less accessible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation